Pengembangan Multimedia 3 Dimensi Sebagai Sarana Pembelajaran - Eridani, Dania; Arfan, M (Jurnal Sistem Komputer, 2016)
The rapid development of technology makes computer and gadget change into devices used to solve almost all of people activities. The use of multimedia as a learning tools is getting more popular as the development of technology. Nowadays, every people has computer and gadget, we can see people always holding gadget everywhere. One type of multimedia is a game. Game is a set of rules that have a goal which purpose is to make its user having fun. Game has positive and negative influence for it user. People love to play game. By this habit, we can use game as multimedia to be a learning tool to make positive use of computer and gadget. Multimedia as a learning tool can be built using 3D based model to gain the interest of its learner. This research shows the process of developing 3D multimedia as a learning tool by using Blender and Unity 3D.